Treatment of Glioblastoma Using Multicomponent Silica Nanoparticles. Issue 11 (4th September 2019) - Turan, Oguz; Bielecki, Peter A.; Perera, Vindya; Lorkowski, Morgan; Covarrubias, Gil; Tong, Kathleen; Yun, Aaron; Loutrianakis, Georgia; Raghunathan, Shruti; Park, Youngjun; Moon, Taylor; Cooley, Shane; et al.
Abstract: Glioblastoma multiforme (GBM) remains highly lethal. This partially stems from the presence of brain tumor initiating cells (BTICs), a highly plastic cellular subpopulation that is resistant to current therapies. In addition to resistance, the blood–brain barrier limits the penetration of most drugs into GBMs. To effectively deliver a BTIC‐specific inhibitor to brain tumors, a multicomponent nanoparticle, termed Fe@MSN, which contains a mesoporous silica shell and an iron oxide core, is developed. Fibronectin‐targeting ligands direct the nanoparticle to the near‐perivascular areas of GBM. After Fe@MSN particles are deposited in the tumor, an external low‐power radiofrequency (RF) field triggers rapid drug release due to mechanical tumbling of the particle resulting in penetration of high amounts of drug across the blood–brain tumor interface and widespread drug delivery into the GBM. The nanoparticle is loaded with the drug 1400W, which is a potent inhibitor of the inducible nitric oxide synthase (iNOS). It is shown that iNOS is preferentially expressed in BTICs and is required for their maintenance. Using the 1400W‐loaded Fe@MSN and RF‐triggered release, in vivo studies indicate that the treatment disrupts the BTIC population in hypoxic niches, suppresses tumor growth and significantly increases survival in BTIC‐derived GBM xenografts. Abstract : The reported nanoparticle is comprised of an iron oxide core surrounded by a drug‐loaded mesoporous silica shell. An external low‐power radiofrequency field makes the nanoparticle vibrate, which facilitates the liberation of drug molecules from the silica shell resulting in widespread drug delivery in hypoxic regions of brain tumors.